2021
DOI: 10.7150/thno.56541
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 ameliorates cognitive deficits via regulation of NMDAR expression in an Alzheimer's disease animal model

Abstract: Background: Abnormal tau accumulation in the brain has a positively correlation with neurodegeneration and memory deterioration, but the mechanism underlying tau-associated synaptic and cognitive impairments remains unclear. Our previous work has found that human full length tau (hTau) accumulation activated signal transducer and activator of transcription-1 (STAT1) to suppress N-methyl-D-aspartate receptors (NMDARs) expression, followed by memory deficits. STAT3 also belongs to STAT protein family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…It has been extensively reported that tau accumulation induces neuron loss and synaptic impairments, which are closely related to cognitive deficits in AD ( Iqbal and Grundke-Iqbal, 2002 ; Giannakopoulos et al, 2003 ; Yin et al, 2016 ). We also found that overexpression of hTau or P301L hTau activated STAT1 and inactivated STAT3 to inhibit the expression of NMDARs, thus inducing dendritic plasticity deficits, including LTP suppression and spine density decrease, and memory deficits ( Li et al, 2019 ; Hong et al, 2020 ; Wan et al, 2021 ). In this study, PINK1 overexpression rescued neuron loss and synaptic damage, and ameliorated cognitive impairments by promoting the degradation of accumulated tau in the autophagy pathway, reducing tau accumulation in mitochondria and alleviating mitochondrial disorders.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…It has been extensively reported that tau accumulation induces neuron loss and synaptic impairments, which are closely related to cognitive deficits in AD ( Iqbal and Grundke-Iqbal, 2002 ; Giannakopoulos et al, 2003 ; Yin et al, 2016 ). We also found that overexpression of hTau or P301L hTau activated STAT1 and inactivated STAT3 to inhibit the expression of NMDARs, thus inducing dendritic plasticity deficits, including LTP suppression and spine density decrease, and memory deficits ( Li et al, 2019 ; Hong et al, 2020 ; Wan et al, 2021 ). In this study, PINK1 overexpression rescued neuron loss and synaptic damage, and ameliorated cognitive impairments by promoting the degradation of accumulated tau in the autophagy pathway, reducing tau accumulation in mitochondria and alleviating mitochondrial disorders.…”
Section: Discussionmentioning
confidence: 70%
“…We injected pAAV-SYN-human Tau-mCherry-3×FLAG-WPRE into the hippocampal CA1 region of mice for 1 month to mimic Alzheimer-like deposits of tau in the brain ( Andorfer et al, 2003 ; Lasagna-Reeves et al, 2011 ; Li et al, 2019 ; Wan et al, 2021 ). Meanwhile, pAAV-SYN-PINK1-EGFP-3×FLAG-WPRE was also co-injected to explore its effect on tau pathology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous report [ 16 ], a novel object recognition test was performed in a box (50 × 50 × 50 cm). First, mouse was put in the box to adapt to the environment for 5 min in an empty box 24 h before testing.…”
Section: Methodsmentioning
confidence: 99%
“…JAK/STAT and NF-kB are two critical pathways involved in the pathogenesis of AD and neuroinflammation. Studies have shown their correlation with microglial activation, and hence, these pathways offer a target for inhibiting microglial activation [58]. α-asarone and tanshinone-I are two naturally occurring bioactive compounds involved in the modulation of the NF-kB pathway and inactivation of microglia (inhibition of M1 polarization) [59].…”
Section: Drugs Targeting Inhibition Of M1 Microglial Polarizationmentioning
confidence: 99%